What Type of Leaders Are We? Understanding and Enhancing Critical Human Resource Development Identity in the United States. (November 2014) - Storberg-Walker, Julia
The Problem: These are the days of grand, interdisciplinary, and global challenges. For example, there is widespread acknowledgment within the scientific community that climate change is happening. The financial meltdown caused thousands of families to lose their homes, and environmental debacles like the BP oil disaster in the Gulf of Mexico generated economic, social, and public health concerns.These are problems—not necessarily human resource development (HRD) problems—but problems nonetheless that impact the people, communities and organizations we lead and serve.We are the leaders, change agents, consultants, and educators whom organizations, communities, and people turn to for their development and training needs. The Solution: I believe HRD scholars should proactively develop a critical orientation to economic, social, cultural, and environmental issues currently plaguing the planet. With such a critical perspective, we can develop a CHRD leadership identity and challenge hidden assumptions and work with others to expose environmental, human, and economicexploitation.The accomplish this goal, I believe, we should examine the historical emergence of critical HRD identities and thenintentionally create critical leadership development opportunities for more HRD professionals to enact critical HRD more of the time. The Stakeholders: Communities, individuals, organizations, the planet.